Design and Implementation 3D Karambol Game Application Using DirectX - Aji Pamungkas; Azhari S Nugradito (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2006)
The 3D game industry in Indonesia is increasing that can be seen by many game centre are always full of customers. But most of the game centre are not using original software because an original one can be very expensive. That is not the only reason, the other reason is that not many Indonesian are developing their own game software. And these increase the use of pirated game software. In this final assignment has been designed and developed, a game application titled 3D Karambol. This application is using DirectX and capable to process karambol game -a tradisional game from Indonesia-, to transform the game objects in 3D world, to do collision detection between those objects and to interact with the users through input device such as keyboard and mouse.